2016
DOI: 10.1007/s11060-016-2254-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of posterior fossa metastases

Abstract: The diagnosis of brain metastases is associated with a poor prognosis reflecting uncontrolled primary disease that has spread to the relative sanctuary of the central nervous system. 20 % of brain metastases occur in the posterior fossa and are associated with significant morbidity. The risk of acute hydrocephalus and potential for sudden death means these metastases are often dealt with as emergency cases. This approach means a full pre-operative assessment and staging of underlying disease may be neglected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 34 publications
1
40
1
Order By: Relevance
“…The posterior fossa harbors 20–30% of all intracranial metastases. [ 10 22 44 47 ] These tumors are often neurologically impairing and potentially life-threatening. The most common primary origin is lung cancer, breast cancer, malignant melanoma, renal cell carcinoma, and colorectal and gynecological cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The posterior fossa harbors 20–30% of all intracranial metastases. [ 10 22 44 47 ] These tumors are often neurologically impairing and potentially life-threatening. The most common primary origin is lung cancer, breast cancer, malignant melanoma, renal cell carcinoma, and colorectal and gynecological cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The most common primary origin is lung cancer, breast cancer, malignant melanoma, renal cell carcinoma, and colorectal and gynecological cancers. [ 44 ] Their clinical presentation and evolution is mainly dependent on the lesion's location and growth rate. Symptoms may arise from focal compression of the cerebellum and vital brainstem nuclei, tonsillar herniation, and increased intracranial pressure due to obstructive hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%
“…The median overall survival (OS) was 6.00 months. The 28 day mortality was 7.6 % (n = 7) with a perioperative morbidity of 22.8 % (n = 21) [24]. Zhang et.al, 2012 observed that the most common primary site of malignancy for brain metastasis was lung (20-40 %) followed by breast (5-17 %) and melanoma (7-11 %) with renal, colorectal and gynecological cancers making up the majority of the remaining [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although the surgeon believed that total resection had been done, it might have been incomplete due to the hindrance of the small and deep surgical field of cerebellum. Sunderland et al 17) reported that a significant increase of leptomeningeal metastasis with cerebellar tumor removed via a piecemeal approach compared with an en block resection. However, our data showed similar local control according to the methods of tumor removal in both supratententorial and cerebellar tumors.…”
Section: Discussionmentioning
confidence: 99%